2019
DOI: 10.1177/2325967119852896
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction Internal Fixation of Medial Epicondyle Fractures After Ulnar Collateral Ligament Reconstruction in Professional Baseball Pitchers

Abstract: Background: Ulnar collateral ligament reconstruction (UCLR) is a common procedure among professional baseball pitchers. An uncommon complication after UCLR is a fracture of the medial epicondyle at the level of the humeral tunnel, which requires open reduction internal fixation (ORIF). Purpose/Hypothesis: The purpose of this study was to determine the performance upon and rate of return to sport (RTS) in professional baseball pitchers after ORIF of the medial epicondyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Performance data were analyzed as previously described with this data set. 5,9 Preoperative and postoperative data were then compared using the paired Student t test and related-samples Wilcoxon signed-rank test as appropriate based on data normality. For each player, maximum preoperative and postoperative levels of play were determined, and each player was then determined to have either returned to the same or a higher level of play, returned but to a lower level of play, or not have returned to play.…”
Section: Methodsmentioning
confidence: 99%
“…Performance data were analyzed as previously described with this data set. 5,9 Preoperative and postoperative data were then compared using the paired Student t test and related-samples Wilcoxon signed-rank test as appropriate based on data normality. For each player, maximum preoperative and postoperative levels of play were determined, and each player was then determined to have either returned to the same or a higher level of play, returned but to a lower level of play, or not have returned to play.…”
Section: Methodsmentioning
confidence: 99%
“…15 HITS has been used in several previous studies and has been found to be a reliable source of information. 2,4,5,9,10 The second dataset was a record of player usage between 2011 and 2017. Each player was assigned a unique ID, linking the 2 datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Relative indications are controversial and can include concomitant ulnar nerve dysfunction, associated elbow dislocation, significant fracture fragment displacement, and injuries in high-level throwing athletes. Erickson et al 6 studied the return to play and performance of professional baseball pitchers after ORIF of the medial epicondyle, seen as a sequela after ulnar collateral ligament reconstruction. They found that 73% were able to return to sport; however, only 55% were able to pitch at the same level or higher.…”
mentioning
confidence: 99%